The role of the teachers' centre in the professional development and in-service training of teachers with specific reference to the East London Teachers' Centre - Badenhorst, John Henry (Rhodes University, Faculty of Education, Department of Education, 1992)
Teachers' Centres are one of the means whereby teachers needs for in-service education and training (Inset) can be met. The professional basis of Teachers' Centres as providers of in-service education and training derives from the need of teachers to develop professionally throughout their careers. Aspects which need to be considered are the need for professional growth and the professional nature of teaching. The effective provision of in-service training requires a knowledge of effective in-service training practise and the barriers that could be encountered in presenting it. Central to any Inset for teachers would be the teachers' needs for such activity. Following on a general statement of teachers needs for Inset the role of the Teachers' Centre in meeting these needs will be examined. Teachers' Centres have specific advantages in meeting certain areas of need for Inset by teachers. A knowledge of the professional activities of teachers activity and methods of establishing the needs for Inset of teachers should promote the effective provision of these programmes. The teacher as an adult learner is important to effective Teachers' Centre operation and the nature of adult learning and variables which affect it will determine the Teachers' Centre reaction in providing Inset. Subject study group activity is very important in Teachers' Centres in the Cape Province and the principles involved in their operation together with practical considerations regarding their operation are important in the provision of Inset. The practical application of theory is illustrated by examples from the East London Teachers' Centre with an emphasis on organisation and the creation of a climate within the Centre for the existence of study groups. The presentation methods used in these study group activities are important and will vary according to the needs of the study group. The selection of methods together with the organisation of presentations and practical methods used in presentation will have an important effect on how they operate. Teachers' Centres have a role to play in promoting change and innovation in schools. The theories of promoting innovation and the roles of the change agent are important. Practical examples from the East London Teachers' Centre are provided. This research, thus, provides a theoretical study of the role of Teachers' Centres in meeting some of the inset needs of teachers as well as practical examples of such activities.
Keywords: Teachers -- In-service training -- South Africa; Education -- South Africa -- East London; Professional education -- South Africa; Educational change -- South Africa